A Robust Polyionized Hydrogel with an Unprecedented Underwater Anti‐Crude‐Oil‐Adhesion Property. Issue 26 (9th May 2016) - Gao, Shoujian; Sun, Jichao; Liu, Pingping; Zhang, Feng; Zhang, Wenbin; Yuan, Shiling; Li, Jingye; Jin, Jian
Abstract : A polyionized hydrogel polymer (sodium polyacrylate‐grafted poly(vinylidene fluoride) (PAAS‐g‐PVDF)) is fabricated via an alkaline‐induced phase‐inversion process. PAAS‐g‐PVDF coatings exhibit unprecedented anti‐adhesion and self‐cleaning properties to crude oils under an aqueous environment. A PAAS‐g‐PVDF‐coated copper mesh can effectively separate a crude oil/water mixture with extremely high flux and high oil rejection driven by gravity, and is oil‐fouling‐free for long‐term use.